A chamada à formação do cidadão: governamentalidade no Ensino de Ciências - Herculano, Bruna Gabriela Nico Pereira (Universidade Federal de São Carlos, 2026)
This thesis investigates how the Teaching of Sciences was constituted as a field of dispute around the formation of the citizen. Inspired by the philosophy of difference, mainly Michel Foucault’s genealogical perspective, in dialogue with Gilles Deleuze, it analyzes statements present in official documents and productions from the field itself, articulating them with events in the history of Brazilian education. From this movement, through a genealogical gesture, it analyzes the historical and discursive conditions that made possible the articulation between Teaching of Sciences and the formation of the citizen in Brazil, questioning the ways in which this relationship participates in the production and modulation of specific subjectivities. It starts from the hypothesis that Teaching of Sciences operates in the service of a governmental rationality whose sign is citizenship, which, in turn, operates in the subjectivation of bodies, calling on them to constitute themselves as citizen subjects. It observes that the Teaching of Science has sought to format this subject through different adjectives (critical citizen, technical, responsible, among others), while qualifying citizenship itself according to cognitive criteria and competencies informed by scientific knowledge. Public participation is progressively translated as the ability to interpret data, evaluate evidence, and make rational decisions, leading citizenship to operate as a regulatory axis of the educational experience. Instead of proposing a new definition of citizenship, the thesis shifts the debate to problematize what citizenship does within the field, a critique that should not be confused with discourses of institutional delegitimization of the school; rather, it seeks to make explicit the mechanisms that operate in the countryside, in order to sustain the school as a public territory of dispute and invention. Finally, it proposes a theoretical, non prescriptive experimentation which questions the possibility of a Teaching of Sciences as re-existence: approximated to the Foucaultian notion of counter-conduct, it is a reading mode that examines the internal variations of the rationality of citizenship in the field. By evidencing displacements, fissures and rearrangements that occur within these rationalities, the thesis expands the possibilities of understanding the Teaching of Sciences, indicating that, even within the school apparatus, cracks emerge through which one can re-exist in the school.
The call for formation of the citizen: governmentality in Science Education
Keywords: Ensino de Ciências;; Governamentalidade; Cidadania; Re-existência; Subjetivação; CIENCIAS HUMANAS::EDUCACAO; 4. Educação de Qualidade